Shaping of a Dual Membrane SOFC and First Electrochemical Tests in a Dedicated 3-Chamber Set-up. (2nd June 2015) - Masson, David; Perrozzi, Francesco; Piccardo, Paolo; Viviani, Massimo; Pilot, Claire; Stoynov, Zdravko; Vladikova, Daria; Chesnaud, Anthony; Thorel, Alain
Abstract : The present paper offers a discussion about an innovative dual membrane fuel cell concept IDEAL-Cell operating between 600°C-700°C. It is based on the junction of SOFCs anodic part with PCFCs cathodic part through a mixed H + and O 2- conducting porous membrane. This concept was successfully proved and developed during the 4 years of a FET-Energy/FP7 project, through the collaboration between 10 European research and technological institutes. After two stages of development, respectively the proof of concept and the realization of an optimized lab-scale cell, the concept has evolved to a simplified design, called "monolithic", in which the mixed H + and O 2- conduction of BCY15 is exploited for the fabrication of all the cell components. With the reduction of chemical gradients and thermal expansion mismatches, the cell durability is potentially enhanced. Furthermore, the shaping, the microstructure and the catalytic properties of the central membrane (CM) have been improved by structuring the central membrane with a Ni foam or by including Pt nano-particles. This work presents a complete study of the permeability of the central component of this concept in view of a reversible SOFC/SOEC operation, and the preliminary results obtained on this new Ni-foam based architecture by using a 3-chambers set-up (Real Life Tester) to determine the electrochemical performances of the cell in real operating conditions.